Into the Grey Zone: Retired Nurses’ Reflections on Ethics in Canadian Nursing Practice - Jones-Bonofiglio, Kristen; Alzghoul, Manal (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Context: Nurses are often hesitant to talk about ethical issues in their practice for many unique and valid reasons. What if the burden of risk was lifted upon retirement, even if just slightly? The purpose of this study was to explore retired nurses’ reflections on their experiences of ethical issues and decision making in various nursing practice settings throughout their careers and to glean recommendations for ethics in contemporary nursing practice. Methods: Data were collected via in-depth, individual, semi-structured interviews. Guided by an interpretive, descriptive approach, data were managed with NVivo v.11 and analyzed with an inductive, comparative, thematic approach. In northern Ontario, two nurse researchers co-interviewed eight retired nurses with decades of practice experience across diverse Canadian health care settings. Ethics approval was obtained through Lakehead University’s Research Ethics Board. Findings: Three themes emerged to address ethical issues in practice; these are creativity, resourcefulness, and a strong sense of community with other nurses. Further, the retired nurses’ collated reflections on ethics in practice are presented as the FIG model: Fellowship, Ingenuity, and Gumption. Conclusions: This study identifies ethical underpinnings that retired nurses have used to effectively respond to ethical issues in their practice. Those who are currently nursing, and nursing as a profession, may wish to recognize and retain these strategies in order to continue to deliver a high standard of quality, ethical care. Recommendations for practice, research, and education are offered.